Study of Dam-break Due to Overtopping of Four Small Dams in the Czech Republic - Alhasan, Zakaraya; Jandora, Jan; Říha, Jaromír (Mendel University in Brno, 2015)
Dam-break due to overtopping is one of the most common types of embankment dam failures. During the floods in August 2002 in the Czech Republic, several small dams collapsed due to overtopping. In this paper, an analysis of the dam break process at the Luh, Velký Bělčický, Melín, and Metelský dams breached during the 2002 flood is presented. Comprehensive identification and analysis of the dam shape, properties of dam material and failure scenarios were carried out after the flood event to assemble data for the calibration of a numerical dam break model. A simple one-dimensional mathematical model was proposed for use in dam breach simulation, and a computer code was compiled. The model was calibrated using the field data mentioned above. Comparison of the erodibility parameters gained from the model showed reasonable agreement with the results of other authors. This study was supported by the Specifi c Research Project No. FAST-J-14-2382 of the Brno University of Technology, Faculty of Civil Engineering and by the project TA 04020670 of the Technology Agency of the Czech Republic.

Dam-break due to overtopping is one of the most common types of embankment dam failures. During the floods in August 2002 in the Czech Republic, several small dams collapsed due to overtopping. In this paper, an analysis of the dam break process at the Luh, Velký Bělčický, Melín, and Metelský dams breached during the 2002 flood is presented. Comprehensive identification and analysis of the dam shape, properties of dam material and failure scenarios were carried out after the flood event to assemble data for the calibration of a numerical dam break model. A simple one-dimensional mathematical model was proposed for use in dam breach simulation, and a computer code was compiled. The model was calibrated using the field data mentioned above. Comparison of the erodibility parameters gained from the model showed reasonable agreement with the results of other authors. This study was supported by the Specifi c Research Project No. FAST-J-14-2382 of the Brno University of Technology, Faculty of Civil Engineering and by the project TA 04020670 of the Technology Agency of the Czech Republic.
Study of Dam-break Due to Overtopping of Four Small Dams in the Czech Republic
Keywords: dam-break; embankment dam; numerical model; dam overtopping; peak discharge.; dam-break; embankment dam; numerical model; dam overtopping; peak discharge.